Adolescents’ lived experience of panic disorder: an interpretative phenomenological analysis - Holly J. Baker; Amelia Hollywood; Polly Waite (BMC Psychology, 2022)
Abstract Background Panic disorder is a debilitating anxiety disorder that has a serious impact on adolescents’ social and academic functioning and general wellbeing. Panic disorder is experienced by around 1 to 3% of the adolescent population. The aim of this study was to examine adolescents’ experiences of having panic disorder. Methods Semi-structured interviews were conducted with eight adolescents with a primary diagnosis of panic disorder. Interpretative Phenomenological Analysis was used to gain an understanding of adolescents’ lived experience of panic disorder. Results Two superordinate themes were identified: (1) Drowning in sensations, and (2) An unacceptable self. The findings show that adolescents experience panic disorder as extremely overwhelming and unpleasant, with debilitating feelings of drowning in sensations. Adolescents’ experiences largely fit with the cognitive model of panic, in which catastrophic misinterpretation of bodily sensations is associated with anxiety, avoidance, and safety behaviours, creating a vicious cycle. Attempts to avoid or prevent the attacks appear to inadvertently make them worse. Social worries, feeling broadly misunderstood, and unhelpful responses from others, contributed to feelings of being different or abnormal and were connected to a negative self-concept. Negative social interactions with teachers and peers in the school environment were particularly damaging. Conclusions These findings offer new insight into these adolescents’ lived experience of panic disorder and highlight the need for adolescents to access timely, evidence-based treatment, as well as the need for increased awareness and understanding of panic disorder in schools.